2014
DOI: 10.1111/acer.12538
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Infusion in the Wake‐Promoting Basal Forebrain Enhances Alcohol‐Induced Activation of Nucleus Accumbens

Abstract: Background Nicotine and alcohol co-abuse is highly prevalent. Recently, we have shown that nicotine infusion in the basal forebrain (BF) increases alcohol consumption. Since nucleus accumbens (NAc) is the terminal brain region associated with drug addiction, we hypothesize that nicotine infusion in the BF may enhance alcohol induced activation of NAc. Methods Adult male Sprague-Dawley rats were surgically implanted with bilateral guide cannulas in the BF. Following post-operative recovery, rats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…; Sharma et al . ). Furthermore, in vitro studies using similar doses of nicotine have demonstrated nicotine induced neuronal activation in sleep‐wakefulness regulatory centers (Li et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Sharma et al . ). Furthermore, in vitro studies using similar doses of nicotine have demonstrated nicotine induced neuronal activation in sleep‐wakefulness regulatory centers (Li et al .…”
Section: Discussionmentioning
confidence: 97%
“…The nicotine dose [75 pmol (equivalent to 11 ng of nicotine‐free base)/500 nl/side] was chosen based on our previous study in rats (Sharma et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, pain is inherent with intraperitoneal route of alcohol administration. The 3 g/kg dose of alcohol was chosen because this dose is effective in promoting sleep and activating the reward centers Alaux-Cantin et al 2013;Sharma et al 2014a). The sleep promoting effects of alcohol was confirmed pre-lesion.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also show that ethanol has differential effects on the NAc core and the shell. In the NAc shell ethanol alters dendrite morphology [ 54 ], cFos expression [ 55 ] and gamma amino butyric acid (GABA) [ 56 ] and dopamine [ 57 ] signaling. Whereas, in the NAc core ethanol exposure alters dendrite morphology [ 53 ], glutamate signaling [ 51 , 52 , 53 ] and mitogen-activated protein kinase (MAPK) expression [ 47 ].…”
Section: Auds and The Nucleus Accumbensmentioning
confidence: 99%